Design of Buried Reinforced Concrete Pipes with SIDD Type IV Installation - Kilic, Havvanur; Demirci, Onur (TURKISH CHAMBER CIVIL ENGINEERS, 2022)
One of the most common and widely used methods of buried reinforced concrete pipe design is the direct design method (SIDD) which was started being developed in 1970's. In SIDD Type IV pipe installation, there is no need to use a special bedding material under the pipe invert because a rock material is used in foundation soil. In this study, the behavior of the buried reinforced concrete pipe with SIDD Type IV installation is investigated. In this scope, a parametric investigation was conducted with numerical analysis to design a concrete pipe considering soil-structure interaction concept. In numerical analysis, the effects of varying design parameters are investigated such as properties like burial depths and diameter of pipes. Therefore, a reinforcement area chart has been created according to the SIDD Type IV design calculation results which includes internal forces obtained from pipe cross section. Furthermore, these obtained reinforcement areas are compared with reinforcement areas used by Iller Bankasi A.S which are widely used in our country for buried pipe design. Hence, the main scope is to design concrete pipes practically by using this chart for SIDD Type IV conditions.
Keywords: Buried reinforced concrete pipes; finite element analysis; direct design; Engineering